Geopolitical dimensions of the Andean FTA with the United States. Some hypotheses to start a reflection - Montúfar, César (2016)
This article analyses geopolitical features of the US-Andean Free Trade Agreement. It considers whether US geopolitics determines the pace of trade negotiations or whether the advance of trade objectives is in fact the main US objective in the Andean Region. As such, three questions are addressed: what geopolitical consequences could the US-Andean Free Trade Agreement have in the region? How is this agreement related to the US's security strategy for the Andean Region?, and Is the negotiation process driven by the US security policy, the trade policy or by Plan Colombia?